Gangguan Berbahasa Tokoh Dodo Rozak pada Film Miracle in Cell No. 7 Versi Remake Indonesia Kajian Psikolinguistik: Language Disorder of the Character Dodo Rozak in the Film Miracle in Cell No. 7 Indonesian Remake Versions Psycholinguistic Studies - Purnama, Ahmad Ri'i Nanda; Kinanti, Kingkin Puput (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2024)
This research delves into the language disorders portrayed by Dodo Rozak in the Indonesian film "Miracle in Cell No. 7," examining how individuals with intellectual disabilities interact linguistically. Grounded in psycholinguistics, the study employs a qualitative descriptive approach to analyze phonological, morphological, and syntactic deviations stemming from disrupted language development, often attributed to brain hemisphere impairments. Data, gathered through attentive listening and meticulous note-taking, were scrutinized utilizing matching techniques, specifically PUP and HBB. The findings illuminate a spectrum of linguistic errors. Phonological anomalies included phoneme alterations, omissions, and substitutions. Morphological irregularities manifested as incorrect affixation. Syntactic errors were evident in sentences that strayed from conventional language structures. This study underscores the film's depiction of language impairments, offering valuable insights into the specific linguistic challenges encountered by individuals with intellectual disabilities, and enriching our comprehension of psycholinguistic phenomena within the realm of cinematic representation. The study contributes to a deeper understanding of language disorders in a real world context.